2022
DOI: 10.1007/s12560-021-09507-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Sequencing of Multiple Human Norovirus Genotypes from Imported Frozen Raspberries Linked to Outbreaks in the Province of Quebec, Canada, in 2017

Abstract: Human noroviruses are among the main causes of acute gastroenteritis worldwide. Frozen raspberries have been linked to several norovirus food-related outbreaks. However, the extraction of norovirus RNA from frozen raspberries remains challenging. Recovery yields are low and PCR inhibitors limit the sensitivity of the detection methodologies. In 2017, 724 people from various regions of the Province of Quebec, Canada, were infected by noroviruses and the outbreak investigation pointed to frozen raspberries as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…However, there remains room for improvement with respect to the tools and standardized methodologies that are available to manage viral foodborne outbreaks. While much work has been conducted to date to understand the limits of shotgun metagenomics and amplicon-based sequencing for genotypic characterization of norovirus in foodstuffs ( 32 , 33 ), there has been only one bioinformatic study to date ( 18 ). Importantly, this single study did not focus on amplicon-based approaches or foodstuffs.…”
Section: Discussionmentioning
confidence: 99%
“…However, there remains room for improvement with respect to the tools and standardized methodologies that are available to manage viral foodborne outbreaks. While much work has been conducted to date to understand the limits of shotgun metagenomics and amplicon-based sequencing for genotypic characterization of norovirus in foodstuffs ( 32 , 33 ), there has been only one bioinformatic study to date ( 18 ). Importantly, this single study did not focus on amplicon-based approaches or foodstuffs.…”
Section: Discussionmentioning
confidence: 99%
“…(2015)Raspberries5724NRNRRaymond et al. (2022)Raspberries13900NRNRSarvikivi et al. (2012)Raspberries4151NRSaupe et al.…”
Section: Appendix E – Summary Of Food‐borne Outbreak Data Retrieved F...mentioning
confidence: 99%
“…A few studies have applied HTS-based methods for the detection and characterisation of norovirus in complex matrices such as food or wastewater (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Notwithstanding these studies, the performance of the various methods, whether it be shotgun metagenomics, capture probe hybridisation, long-read sequencing or amplicon-based HTS, has varied.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these challenges, several recent studies have demonstrated the capability of various amplicon HTS assays for the genotypic characterisation of norovirus in shellfish (5,17), with similar success observed in berry samples (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation